2019
DOI: 10.2196/13253
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Long-Term Trajectories in Web-Based Happiness Interventions: Secondary Analysis From Two Web-Based Randomized Trials

Abstract: Background A critical issue in understanding the benefits of Web-based interventions is the lack of information on the sustainability of those benefits. Sustainability in studies is often determined using group-level analyses that might obscure our understanding of who actually sustains change. Person-centric methods might provide a deeper knowledge of whether benefits are sustained and who tends to sustain those benefits. Objective The aim of this study was to conduct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…For instance, a comprehensive review of two large longitudinal data sets revealed that individuals who participated in online interventions were able to maintain their levels of well-being for several months. In particular, those who initially reported lower levels of well-being and continued to actively participate were more likely to experience lasting positive outcomes ( Sanders et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a comprehensive review of two large longitudinal data sets revealed that individuals who participated in online interventions were able to maintain their levels of well-being for several months. In particular, those who initially reported lower levels of well-being and continued to actively participate were more likely to experience lasting positive outcomes ( Sanders et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mental wellbeing can be defined as a state of optimal positive functioning that is related but independent from mental illness (World Health Organization, 2004 ). States of mental wellbeing are not only desirable in the general population (Parks et al, 2012 ; Sanders et al, 2019 ), but also associated with increased longevity (Martín-María et al, 2017 ) and health (Kushlev et al, 2020 ), improved work productivity (Gandy et al, 2016 ; Hamar et al, 2015 ), and resilience against mental illness (Grant et al, 2013 ; Iasiello et al, 2019 ; Lamers et al, 2015 ). Many people actively seek out methods to improve their mental wellbeing (Parks et al, 2012 ; Sanders et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…States of mental wellbeing are not only desirable in the general population (Parks et al, 2012 ; Sanders et al, 2019 ), but also associated with increased longevity (Martín-María et al, 2017 ) and health (Kushlev et al, 2020 ), improved work productivity (Gandy et al, 2016 ; Hamar et al, 2015 ), and resilience against mental illness (Grant et al, 2013 ; Iasiello et al, 2019 ; Lamers et al, 2015 ). Many people actively seek out methods to improve their mental wellbeing (Parks et al, 2012 ; Sanders et al, 2019 ). Developing evidence-based interventions that are accessible to the general population is important to help individuals promote their own wellbeing and improve life satisfaction, health, and productivity of the general population.…”
Section: Introductionmentioning
confidence: 99%